First clinical experience of isatuximab safety and tolerability in relapsed and refractory multiple myeloma: real-world data from a compassionate use program in Germany - Leitner, Theo; Khandanpour, Cyrus; Wendelin, Knut; Oduncu, Fuat; Kimmich, Christoph; Naumann, Ralph; Kull, Miriam; Goldschmidt, Hartmut; Ehmer, Martin; Kiewitz, Claudia; Salwender, Hans (Frontiers in Hematology, 2024)
Therapy for relapsed and refractory multiple myeloma (RRMM) remains challenging. While monoclonal antibodies against CD38 combined with pomalidomide have demonstrated efficacy in clinical trials, real-world data remain sparse. We present real-world data from a compassionate use program (CUP) of isatuximab given in combination with pomalidomide and dexamethasone according to the German Compassionate Use Directive ahead of commercial availability for adult patients with RRMM. Patients had received at least two prior lines of therapy, including lenalidomide and a proteasome inhibitor (PI), and had demonstrated disease progression on the last therapy. Isatuximab was administered as part of the clinical routine. In total, 18 patients were included in the CUP before the official market availability of isatuximab. The data reflect a heterogeneous population in terms of age, risk factors, previous diseases, and treatments. Most of the patients had received two full isatuximab cycles. The analysis showed no new safety signals, supporting the manageable toxicity profile of isatuximab and highlighting its potential in real-world settings.